Between Tradition and Reform: Maqāṣid al-Sharīʿah and the Transformation of Islamic Family Law in Indonesia - Wa Ode Zuliarti; Muhammad Ibnu Rasyid; Novita Aliasari; Akmal Surianto; Muhammad Yusuf Mutahir; Mustika Mustika; Muhammad Luthfi; Muhammad Rayhan Pratama; Nailah Nailah (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Islamic family law in Indonesia is undergoing profound transformation, navigating tensions between classical fiqh, national legislation, and contemporary demands for gender justice and human rights. Central to this transformation is Maqāṣid al-Sharīʿah, the objectives-based framework of Islamic jurisprudence, which has emerged as the primary normative instrument for legitimizing and directing legal reform in areas including marriage, divorce, child custody, and property rights. Objectives: This study examines how Maqāṣid al-Sharīʿah functions as a jurisprudential foundation for reforming Indonesian Islamic family law, with particular focus on the elevation of the minimum marriage age, mandatory civil registration, and post-divorce property rights. Method: A qualitative doctrinal-legal design was employed, combining normative analysis of primary legal texts (Law No. 1/1974, Law No. 16/2019, and the KHI) with a purposive review of 24 peer-reviewed international sources. Data were analyzed thematically using a three-layered hermeneutical framework grounded in the five essential maqāṣid objectives. Results: Findings reveal that each legislative reform aligns coherently with the maqāṣid principles of preserving life, lineage, intellect, and property: the age amendment reduces maternal mortality and child poverty; mandatory registration safeguards women’s and children’s legal personhood; and codification of marital joint property prevents post-divorce economic dispossession. Conclusion: Indonesian Islamic family law reform exemplifies a “third pathway” progressive maqāṣid jurisprudence that remains anchored in classical Islamic legal tradition while generating outcomes that protect human dignity and converge with international human rights standards, offering a replicable model for Muslim-majority states navigating analogous reform pressures. Keywords: maqāṣid al-sharīʿah; Islamic family law; legal reform; gender justice